FACTORS CONTRIBUTING PROLONGED HOSPITAL STAY IN POST- SURGICAL PATIENTS: A COMPREHENSIVE ANALYSIS (Journal of Medical & Health Sciences Review, 2025)
Background of study: Hospital patients after surgery face a major challenge for healthcare facilities and patient recovery outcomes because of extended hospital durations. Knowledge about hospital stay duration determinants enables healthcare providers to build specific interventions which support patient healing and make better use of hospital resources. Objective of study: The main objective was to analyze the factors linked with increased hospital stay among the post-operative patients.Material &Methodology: This descriptive cross-sectional study was conducted in different surgical wards of Sheikh Zayed Hospital, Lahore. Different surgical patients fulfilling criteria for this study were sampled through convenience methods. The investigators excluded patients who did not provide complete data along with those in requiring emergency surgery. Clinical Performa recorded all surgical patient demographic information alongside clinical features and operative data to study factors contributing to prolonged hospitalization. The researchers analyzed their gathered data through version 23.00 of the SPSS software package. Researchers measured the scores from each factor and evaluated their links and statistical connections with the patients' hospital stay duration.Results: Analysis of 160 participants showed prolonged hospitalization among 18.75% of patients. Patient demographics revealed 13% within the 31-35 age bracket followed by 15.6% of subjects aged 50-55 years with female patients representing 46% of the study group and males comprising 54% of participants. The hospital stay duration for patients with complications reached 12.6 days and the difference was statistically significant (P < 0.001). Postoperative complications along with delayed wound healing, comorbidities, ICU stay, increased operative time, complex surgery ≥100 minutes, preoperative anemia, patient age rise, and severe postoperative pain were shown to cause longer hospital stays for patients. Postoperative complications resulted in a prolonged hospital stay by +13.2 days in cases of wound breakdown and +14.3 days when HAP developed and +13.8 days when pain intensified. The relationship between surgical site infection and extended hospital stay showed strong correlation based on the comorbidity score of 6.0 while previous hospital admission scored 5.0 and surgical site infection scored 8.0. The severity score for Hospital-acquired pneumonia reached 9.0 making it a critical risk factor. Medical patients who experienced pain at level three or higher demonstrated prolonged hospital stays for discharge readiness.Conclusion: The research established important risk factors including patient age combined with existing health conditions and surgical postoperative problems alongside patient-reported pain levels and hospital-acquired infections and intensive care requirements. Hospital stay duration prediction becomes more accurate through both structured risk assessment structures and classification systems that identify high- risk patients.